2011
DOI: 10.1111/j.1744-7348.2011.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physiological sexual dimorphism estimated from three-dimensional virtual trees of yerba-mate (Ilex paraguariensis) is modified by cultivation environment

Abstract: Yerba-mate is a subtropical, evergreen, dioecious, South American tree. Sexual dimorphism in photosynthesis, leaf allometry and foliage distribution was hypothesised. Virtual trees (constructed in VPlants software from detailed measurements of plant morphogenesis) of the two genders were compared considering two contrasted cultivation environments and three developmental stages. The total crown volume, leaf area per plant (LA), leaf area index (LAI) and leaf area density (LAD) were calculated. The light interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Yerba‐mate leaves and thin branches are used for beverages, foods, supplements, pharmacological products, nutraceuticals and cosmetics products (Chaicouski & Lazzarotto, 2021; Gerber et al, 2023). Yerba‐mate plants are grown in monoculture (MO; Rakocevic et al, 2011), with cover crops (Heck et al, 2008), and also in agroforestry systems (AFS), under shading in the understory (Rakocevic et al, 2011), or even in semi‐hydroponic systems (Aguiar et al, 2022). For production of leaf biomass, pruning is carried out during growth pauses, every 18 or 24 months.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yerba‐mate leaves and thin branches are used for beverages, foods, supplements, pharmacological products, nutraceuticals and cosmetics products (Chaicouski & Lazzarotto, 2021; Gerber et al, 2023). Yerba‐mate plants are grown in monoculture (MO; Rakocevic et al, 2011), with cover crops (Heck et al, 2008), and also in agroforestry systems (AFS), under shading in the understory (Rakocevic et al, 2011), or even in semi‐hydroponic systems (Aguiar et al, 2022). For production of leaf biomass, pruning is carried out during growth pauses, every 18 or 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…If physiological regulation is not achieved, various other strategies can be taken, such that females can breed less frequently than males, reduce growth, biomass production and longevity (Wheelwright & Logan, 2004), or present higher mortality (Popp & Reinartz, 1988). In female plants of yerba‐mate, leaves show higher photosynthesis than in male plants before flowering and fruit maturation (Rakocevic et al, 2009; Rakocevic et al, 2011), while branch growth rates do not differ between females and males, overall (Guédon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment of cultivation, especially the conditions of high or low luminosity and the stage of development can interfere on the sexual expression (RAKOCEVIC et al, 2011). Height and diameter have been the phenotypic characteristics more used as indicators to analyze these changes related to sex, considering that the vegetative vigor is the result of a greater ability to adaptation (PETZOLD et al, 2013).…”
Section: Figurementioning
confidence: 99%
“…Considering the several aspects related to the improvement of the species, the effect of nutritional status of different provenances (OLIVA et al, 2014) and their respective progenies (STURION; RESENDE, 2005;RAKOCEVIC et al, 2005), the sexual dimorphism (male and female plants, (RAKOCEVIC et al, 2011;RESENDE, 2010), the cultivation system (in consortium or homogenous) (CARON et al, 2014) and the cultivation type have showed a strong influence on leaf mass production (RAKOCEVIC et al, 2007;2009). In a similar way, some morphological variations, mainly related to leaves (BASTOS et al, 2014;BORILLE et al, 2005;VALDUGA et al, 2016) were described in Brazil (REISSMANN et al, 2003) and Argentina (JANSSENS;SCHERER, 2011), however, they were not still linked to the productivity of the species.…”
Section: Introductionmentioning
confidence: 99%